1999
DOI: 10.1111/j.1540-6288.1999.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Long Memory In Futures Prices

Abstract: This paper tests for fractional roots in the futures prices for selected commodities, foreign currencies, and stock indexes. The fractional testing method is the spectral regression method suggested by Geweke and Porter-Hudak (1983). The empirical results suggest the presence of a fractional exponent in the differencing process for several commodity and foreign currency futures prices. The returns series for these commodities and currencies exhibit long range positive dependence. However, differencing of exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Corazza et al [16] discussed the fractal structure in agricultural futures markets. Barkoulas et al [17] researched the long memory effect in futures prices. Wei and Raymond [18] applied R/S analysis, modified R/S analysis, and the AFIMA model to discuss the long memory in six agricultural futures markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corazza et al [16] discussed the fractal structure in agricultural futures markets. Barkoulas et al [17] researched the long memory effect in futures prices. Wei and Raymond [18] applied R/S analysis, modified R/S analysis, and the AFIMA model to discuss the long memory in six agricultural futures markets.…”
Section: Introductionmentioning
confidence: 99%
“…For the nonlinear, fractal, and chaotic features in agricultural markets, we refer to the articles [16][17][18][19][20][21][22]. Corazza et al [16] discussed the fractal structure in agricultural futures markets.…”
Section: Introductionmentioning
confidence: 99%
“…Our results 22 See, inter alia, Barkoulas, Labys, and Onochie (1999); Crato and Ray (2000); Yang et al (2001); Baillie, Han, Myers, and Song (2007); Elder and Jin (2007). 23 A 20-year sample period is considered as an appropriate period by recent studies such as Barkoulas et al (1999), Crato and Ray (2000), and Baillie et al (2007).…”
Section: Conventional and Fractional Integration Testsmentioning
confidence: 98%
“…Granger [7] pointed out that over-difference happened when using ARIMA model to deal with data which have long-term memory, therefore proposed autoregressive fractionally integrated moving average (ARFIMA) model. Barkoulas et al [8] computed the fractional difference of futures price of agricultural commodities and found that some futures prices had long-term memory, thus met the requirement of ARFIMA model. ARIMA model ignored the influence of other factors on price.…”
Section: Literature Reviewmentioning
confidence: 99%